Sonography of carpal tunnel syndrome: why, when and how. (June 2012) - Peer, Siegfried; Gruber, Hannes; Loizides, Alexander
Due to technical progress in hardware and software, high-resolution ultrasonography has become one of the most important techniques for imaging of peripheral nerves. Consequently it has become an important adjunct to the work-up of patients with carpal tunnel syndrome. With sufficient knowledge of the normal sonographic appearance of the median nerve/carpal tunnel and the direct pathophysiological expression of compression neuropathy on the sonographic presentation of the median nerve, sonography is complementary to electrophysiological testing in the diagnosis of carpal tunnel syndrome.